2007
DOI: 10.1093/brain/awm035
|View full text |Cite
|
Sign up to set email alerts
|

Locomotor adaptation on a split-belt treadmill can improve walking symmetry post-stroke

Abstract: Human locomotion must be flexible in order to meet varied environmental demands. Alterations to the gait pattern occur on different time scales, ranging from fast, reactive adjustments to slower, more persistent adaptations. A recent study in humans demonstrated that the cerebellum plays a key role in slower walking adaptations in interlimb coordination during split-belt treadmill walking, but not fast reactive changes. It is not known whether cerebral structures are also important in these processes, though s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

36
499
2
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 463 publications
(542 citation statements)
references
References 33 publications
36
499
2
5
Order By: Relevance
“…However, the results did not support this hypothesis. A previous study of split-belt treadmill adaptation in those with chronic stroke found no relationship between the level of sensorimotor impairment and the magnitude of aftereffects in persons with chronic stroke (Reisman et al 2007). Our results extend these findings and demonstrate that learning of a novel locomotor task over days is also not related to the level of sensorimotor impairment after stroke.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…However, the results did not support this hypothesis. A previous study of split-belt treadmill adaptation in those with chronic stroke found no relationship between the level of sensorimotor impairment and the magnitude of aftereffects in persons with chronic stroke (Reisman et al 2007). Our results extend these findings and demonstrate that learning of a novel locomotor task over days is also not related to the level of sensorimotor impairment after stroke.…”
Section: Discussionsupporting
confidence: 79%
“…The split-belt treadmill is a treadmill in which there are two independently controlled belts, one under each foot, that travel at two different speeds. When subjects adapt their walking pattern to these conditions for 10 -15 min, significant asymmetries in step length, double-support times, and limb phase angles are present when normal walking conditions are resumed (Reisman et al 2005(Reisman et al , 2007(Reisman et al , 2009). These responses, of changing interlimb dynamics over a series of steps during one practice period on the rotating or split-belt treadmill, are a form of motor adaptation; participants are adjusting an already well-learned motor skill over a period of trial-and-error practice, as they are exposed to a novel and perturbing environment (Martin et al 1996b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, walking on a split-belt treadmill with the two belts (1 for each leg) running at different speeds disrupts the left-right symmetry (henceforth referred to as "symmetry") of walking. Both temporal symmetry (such as equal durations for comparable periods in the left and right walking cycle) and spatial symmetry (such as equal kinematic excursions of the left and right legs) are disrupted (Reisman et al 2005). Symmetry can be restored with continued stepping on the split-belt treadmill for about 10 min.…”
mentioning
confidence: 99%
“…they help the subject to do the task better. However, research on motor learning has emphasized that errors are fundamental signals that drive motor adaptation [10][11][12]. Previous studies have shown that healthy subjects can adapt to a force perturbation during stepping [13,14].…”
Section: Introductionmentioning
confidence: 99%